Prevalence of resistance-associated viral variants to the HIV-specific broadly neutralising antibody 10-1074 in a UK bNAb-naïve population - Zacharopoulou, Panagiota; Lee, Ming; Oliveira, Thiago; Thornhill, John; Robinson, Nicola; Brown, Helen; Kinloch, Sabine; Goulder, Philip; Fox, Julie; Fidler, Sarah; Ansari, M. Azim; Frater, John (Frontiers in Immunology, 2024)
Broadly neutralizing antibodies (bNAbs) targeting HIV show promise for both prevention of infection and treatment. Among these, 10-1074 has shown potential in neutralizing a wide range of HIV strains. However, resistant viruses may limit the clinical efficacy of 10-1074. The prevalence of both de novo and emergent 10-1074 resistance will determine its use at a population level both to protect against HIV transmission and as an option for treatment. To help understand this further , we report the prevalence of pre-existing mutations associated with 10-1074 resistance in a bNAb-naive population of 157 individuals presenting to UK HIV centres with primary HIV infection, predominantly B clade, receiving antiretroviral treatment.Single genome analysis of HIV proviral envelope sequences showed that 29% of participants' viruses tested had at least one sequence with 10-1074 resistance-associated mutations.Mutations interfering with the glycan binding site at HIV Env position 332 accounted for 95% of all observed mutations. Subsequent analysis of a larger historic dataset of 2425 B-clade envelope sequences sampled from 1983 to 2019 revealed an increase of these mutations within the population over time.Clinical studies have shown that the presence of pre-existing bNAb mutations may predict diminished therapeutic effectiveness of 10-1074. Therefore, we emphasize the importance of screening for these mutations before initiating 10-1074 therapy, and to consider the implications of pre-existing resistance when designing prevention strategies.